THE ROLE OF GEORGE S. COUNTS’ RECONSTRUCTIONISM IN THE IMPLEMENTATION OF DIFFERENTIATED LEARNING IN SENIOR HIGH SCHOOLS - Sumaryono Sumaryono; Akhmad Asnawi; Sugiyono Sugiyono; Endang Fauziati (Education Studies and Teaching Journal (EDUTECH), 2025)
This study aims to explain George S. Counts’ Reconstructionist philosophy, the concept of differentiated learning, and its application within the Reconstructionist perspective in the context of the Merdeka Curriculum. The research employs a library study with a qualitative descriptive approach, using data reduction, presentation, and conclusion drawing techniques. The findings reveal that Counts views education as an agent of social reconstruction that plays an active role in building a democratic and just society. His ideas align with the principles of differentiated learning, which respect students’ diversity, foster critical awareness, and promote social responsibility. The integration of these two concepts forms a humanistic and transformative educational paradigm, where teachers act as facilitators of social change and students become agents of renewal toward a civilized and equitable society.